Spatiotemporal evolution and optimization analysis of investment efficiency in China’s agricultural water conservancy infrastructure based on a two-stage DEA model - Sun, Li; Zhang, Chi; Liu, Qingchun; Xu, Changxin; Song, Min (Frontiers in Earth Science, 2024)
The turbulent international political and economic situation has presented significant challenges to food and water security. Agricultural water conservancy infrastructure has garnered considerable attention due to its crucial role in the allocation and efficient utilization of water resources. Traditional research on the investment efficiency of agricultural water conservancy infrastructure often treats the intermediate impact pathways as a “black box”, neglecting the distinctions among various links. This article employs a two-stage DEA model to partition the impact of agricultural water conservancy infrastructure investment on agricultural output into two stages: water supply and water use. Utilizing data of 31 provinces in China from 2008 to 2022, we measured the efficiency of the two stages, as well as the spatiotemporal distribution and evolution characteristics. The findings reveal a spatial misalignment between water supply and water use efficiency: regions exhibiting higher water supply efficiency in the first stage are primarily those with abundant water resource endowments, whereas water use efficiency in the second stage is closely linked to regional economic development levels. Additionally, the spatial distribution and evolution characteristics of efficiency values indicate that the polarization of water use efficiency is more pronounced, with a significant spatial correlation observed between geographically adjacent areas and those within the same watershed. Conversely, water supply efficiency shows a significant correlation only within the context of watershed relationships. Based on the analysis of the sources of efficiency loss, recommendations include increasing investment in water-saving irrigation technologies, developing agricultural water conservancy infrastructure suitable for large-scale mechanized production, and designing investment compensation mechanisms. Future research is suggested to use econometric models to further examine and identify factors affecting efficiency, particularly the impacts of inter-basin water transfer projects.